Diagnostic value and potential clinical significance of duodenal lipoma based on computed tomography imaging data. Issue 33 (20th August 2021) - Hu, Zhi-Wei; Liang, Pan; Li, Zhi-Li; Li, Ai-Yun; Li, Li-Ming; Liu, Yi-Yang; Feng, Meng-Yun; Gao, Jian-Bo
Abstract: Background: To explore the diagnostic value of computed tomography (CT) imaging for duodenal lipoma and the potential clinical significance of the findings. Methods: Clinicopathological and CT data from 57 patients, who were diagnosed with duodenal lipoma at the first affiliated Hospital of Zhengzhou University (Zhengzhou, China) between June 2014 and March 2019, were retrospectively reviewed. Data collected included location and size of the tumor, morphological manifestations (shape, density, boundary), concomitant diseases, pathology and gastroscopy results, and follow-up. Follow-up was performed via telephone, and surgical patients were followed-up for recurrence, metastasis and tumor size, and morphological changes. The follow-up period was up to January 2019. Results: Of the 57 patients with duodenal lipoma, contrast-enhanced scanning was performed in 7 cases. The tumor was located in the descending duodenum in 33 cases, the ascending in 4 cases, the horizontal in 16 cases, and the bulb in 4 cases. Mean tumor size was 13.0 ± 5.8 mm. CT morphological features of the tumor were as follows: tumor shape, round, quasi-round, or oval (n = 42); long strip (n = 3); nodular (n = 2); triangular (n = 1); and irregular lobulated (n = 9). Among the 57 patients, tumor density was homogeneous in 52 cases, inhomogeneous in 4 cases, and nodular with calcification in 1 case. The tumor boundary was classified as clear and with no capsule. Diseases concomitant with the tumor were as follows: gastritis (n = 23), gastric adenocarcinoma (n = 1), and gastric lymphoma (n = 1). Esophageal disease was found in 16 cases, including reflux esophagitis (n = 12) and esophageal cancer (n = 4). There were 13 cases of gallbladder and biliary disease, including cholecystolithiasis and cholecystitis (n = 9), common bile duct disease (n = 2), colorectal cancer (n = 4), lung cancer (n = 2), duodenal carcinoma with obstruction (n = 1), and ureteral space narrowing (n = 1). Conclusion: CT was an effective, non-invasive method for diagnosis of duodenal lipoma. CT imaging could clearly discern location, size, shape, and nature of duodenal lipomas. Duodenal lipoma can be associated with digestive tract inflammatory diseases and tumors in different locations, and its diagnosis is potentially valuable for their prevention and treatment.